GUI BASED HEALTH MONITORING SYSTEM USING RASPBERRY PI - Paresh Valiya,; Sejal Shinde,; Milind Paraye, (International Journal of Innovations in Engineering Research and Technology, 2021)
Now-a-days health problems like cardiac failure, lungfailuresheart related diseases are arising day by day at a very high rate. Due to these problems time to time health monitoring is very essential. A modern concept is health monitoring of a patient wirelessly. It is a major development in medical arena. Thus paper based on the monitoring of the patient that is done by the doctor continuously without actually visiting the patient. Health professionals have developed a brilliantandinexpensive healthmonitoringsystem for providing more comfortable living to the people suffering from various diseases using leading technologies like wireless communications,wearable andportableremote health monitoring device. As a result, visits of doctors to the patients constantly are decreasedas the information regarding patient’s health directly reaches to doctor’s monitor screen from anywhere the patient resides. Also, based on this doctors can save many lives by imparting them a quick valuable service. In this, IoT is becoming a major platform for many services applications, also using Raspberry Pi not just as a sensor node but also a controller here. Paper propose a generic health monitoring system as astep forwardto the progress made in this department tillnow.